ENHANCING CRITICAL THINKING THROUGH TEACHING LITERATURE IN THE EFL CLASSROOM The Case of teachers of literature of the English department at Ammar Telidji University of Laghouat - Bader Amani Feriel; Gasmi Mustapha (University of Ammar Theledji -Laghouat, 2021)
Teaching literature is an intricate pedagogical practice that requires the integration of techniques, and strategies. The present study aims at finding fruitful teaching strategies to enhance the critical thinking among students of literature. The research problem of this study is: what are the effective strategies in teaching literature that enhance critical thinking, among students of the English department? This study adopts mixed methods which are analytical and descriptive methods, and mixed approaches that are qualitative and quantitative approaches. The samples of this study are teachers of literature who belong to the English department. The questionnaire is the main instrument of this study to test the research hypotheses. The results of the questionnaire highlights that literature enhances the critical thinking among students; the investigation showed that, there are various objectives can be exploited from literature to enhance the critical thinking among students, to develop the critical thinking teachers should be seen as coaches. The main findings of the research are; first there exists different strategies to enhance the critical thinking, but the discussion method is the useful strategy to enhance the critical thinking, second the positive atmosphere prevailing in the classroom helps students to improve their critical thinking, lastly the issues that cannot help teachers to achieve the role of literature which is enhancing the critical thinking are; first lack of motivation among students, students' uneasiness to be motivated to assimilate the lecture, memorizations and over generalizations reduce the improvement of the critical thinking, and lack of reading and depending only on revues and summaries. This work needs to go beyond English department in which we will have a large sample to see the weaknesses as well as the strengths of this subject